The mediating role of pain catastrophizing in the relationship between presurgical anxiety and acute postsurgical pain after hysterectomy - Pinto, Patrícia (2012)
The aim of this study was to examine the joint role of demographic, clinical, and psychological variables 30 as predictors of acute postsurgical pain in women undergoing hysterectomy due to benign disorders. A 31 consecutive sample of 203 women was assessed 24 hours before (T1) and 48 hours after (T2) surgery. 32 Baseline pain and predictors were assessed at T1 and postsurgical pain and analgesic consumption at 33 T2. Several factors distinguished women who had no or mild pain after surgery from those who had mod- 34 erate to severe pain, with the latter being younger, having more presurgical pain, and showing a less 35 favorable psychological profile. Younger age (odds ratio [OR] = 0.90, P < .001), presurgical pain 36 (OR = 2.50, P <.05), pain due to other causes (OR = 4.39, P = .001), and pain catastrophizing (OR = 3.37, 37 P = .001) emerged as the main predictors of pain severity at T2 in multivariate logistic regression. This 38 was confirmed in hierarchical linear regression (b = 0.187, P < .05; b = 0.146, P < .05; b = 0.136, P < .05; 39 b = 0.245, P < .01, respectively). Presurgical anxiety also predicted pain intensity at T2. Findings revealed 40 an integrative heuristic model that accounts for the joint influence of demographic, clinical, and psycho- 41 logical factors on postsurgical pain intensity and severity. In further mediation analysis, pain catastro- 42 phizing emerged as a full mediator between presurgical anxiety and postsurgical pain intensity. The 43 potential clinical implications for understanding, evaluating, and intervening in postsurgical pain are 44 discussed.